Effects of Different Levels of Yucca Supplementation on Growth Rates, Metabolic Profiles, Fecal Odor Emissions, and Carcass Traits of Growing Lambs - Ibrahim S. Alsubait; Ibrahim A. Alhidary; Ahmed A. Al-Haidary (Animals, 2023)
Sixty male Awassi lambs were used to investigate the effects of dietary Yucca schidgera extract (YS) on the production, fecal and urinary odor emissions, and carcass traits of growing lambs fed complete pellets. Lambs were fed either a complete pelleted diet without yucca (control) or supplemented with 300 or 600 mg YS/kg dry matter (DM) during the 84-day experiment. The weights and feed consumption of the lambs were measured weekly. Blood samples were taken on days 1, 28, 58, and 84, and ruminal fluid samples were collected on day 70. On day 90, the odor emissions from feces and urine were measured. On day 84, 12 lambs were slaughtered for the evaluation of carcass and meat quality. The final values for bodyweight, bodyweight gain, and feed efficiency of lambs fed the YS300 diet were 3.40%, 6.64%, and 6.17%, respectively, higher (p < 0.05) than those fed the YS600 diet. Additionally, the percentage of dressing, myofibril fragmentation index, and ruminal isovalerate percentage of lambs treated with YS600 were higher than those treated with YS300. Compared with the control, the addition of yucca reduced odor emissions from feces and urine. In conclusion, dietary YS300 had no additional benefits on growth rate, feed efficiency, and carcass traits, while dietary YS600 improved fecal and urinary odors.